Drоhomyretskyi Ya.M., Dovzhynskyi I.M. The influence of powderlike additives concentration in consistent oil Litol-24 on wearpresisfant of tribosystems. - Дрогомирецький, Я.М.; Довжинський, І.М. (Problems of Tribology, 2014)
Data of the held experiments show that in adding fulleren soot the properties of plastic oil Litol-24 improve in comparison with those ones wilbaont adding it. It should be pointed aut that the most effectivt is 5% concentration of the additive and it influences on the reducing of friction coefficient. As additive phenosan-23 acts more effectivt compared fulleren soot. so, the concentration of the additive influence on the intensity and volumetric wear as friction coefficient and temperature in the friction pair.